Phytochemical screening and high-performance thin-layer chromatography fingerprint profile of three species of leucas (Lamiaceae) - K Geethika; P Sunojkumar (Ancient Science of Life, 2017)
Background: The members of genus Leucas possess high economic potential. As medicinal herbs these were well known as 'Droṇapuhṣpī' in Ayurveda literature. The present study aims to carry out the phytochemical screening as well as the HPTLC fingerprint profiling of three species of Leucas. Materials and Methods: Aqueous, methanol, ethanol and chloroform extracts of each plant were subjected to qualitative phytochemical screening. The total phenols, flavonoids and tannins were quantified in the methanolic extract by standard spectrophotometric methods. HPTLC method for the separation of the active constituents in extracts has been developed and TLC of the methanolic extracts on silica gel pre-coated aluminum plates of Merck by automatic TLC applicator and using solvent system Toluene: ethyl acetate:7:3 was performed. Results: Preliminary phytochemical screening of different extracts showed the presence of different phytoconstituents such as flavonoids, terpenes, tannins, carbohydrates, glycosides, phenolic compounds, proteins and amino acids. Among all the three extracts studied, L. ciliata had the highest concentration of phenolics (34.5 ± 0.35), flavonoids (48.25 ± 1.06) and tannins (6.45 ± 0.5). A HPTLC fingerprint scanned at 550 nm for methanol leaf extracts revealed 12 peaks for L. stelligera, 15 peaks for L. eriostoma and 13 peaks for L. ciliata with Rf values in the range of 0.06 to 0.98.